The Evolution of Zoonosis-Related Studies in Indonesia, 1977-2023: Bibliometric Analysis Concepts - Nurjanah, Diana; Dharmayanti, Indi; Fadilah, Fadilah (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
Various zoonotic diseases have been reported as epidemics throughout the world, including in Indonesia. Various studies have been conducted related to gaps in knowledge, especially on disease distribution, etiology, pathogens, hosts, vector biology, dynamics, cycle of transmission, predisposing factors, and risk factors. To find out the dynamics of zoonotic disease study and research in Indonesia, a study was conducted to report a literature analysis that focused on bibliometric analysis of the Scopus database and VOSviewer software to create a visualization map that identified how the evolution of zoonotic diseases studies from 1977-2023 in Indonesia. In co-occurrence analysis, two units of analysis are used, namely